Factors affecting the abundance of Peters’s squirrel, Sciurus oculatus, in a population of Central Mexico - Jorge Tobajas; José Jímenez; Gerardo Sánchez-Rojas (Revista Mexicana de Biodiversidad)
Peters’s squirrel, Sciurus oculatus, is an endemic species distributed in fragmented populations in Central Mexico, which is one of the most densely populated areas in Mexico. No study has estimated the abundance of this species yet, and the effects of human-environmental factors on its abundance and distribution are unknown. Understanding the role of these factors on its abundance is crucial to its management and conservation. We used the Royle-Nichols model to estimate the abundance and detection probability with detection-non-detection data collected from a camera trap survey. The human-environmental factors that might influence the abundance and distribution of squirrel were modeled. Distance to nearest human settlements had a positive effect on abundance; meanwhile, the presence of the main predator species of the squirrel was a negative factor for detection probability. These findings suggest less abundance or/and a decrease in-ground use in areas with the presence of predators and nearest to human settlements. These results indicate the negative effect of human activities on squirrel abundance and the possible anti-predatory behavior of Peters’s squirrel.